DIFFICULTIES IN ADAPTING TO GLOBAL STANDARDS IN UZBEKISTAN AND WAYS TO OVERCOME THEM (European Journal of Economics, Finance and Business Development, 2025)
Uzbekistan is at a crucial juncture in its economic development, aiming to integrate more closely with the global economy. However, the country faces significant challenges in adapting to international standards due to the legacy of a centrally planned economy, regulatory complexities, cultural factors, and infrastructure deficiencies. This paper explores these difficulties and proposes actionable strategies to facilitate the alignment of Uzbekistan’s industries with global norms. By investing in capacity building, improving regulatory clarity, enhancing infrastructure, and fostering a culture of innovation, Uzbekistan can successfully navigate the transition towards global standards, ultimately promoting sustainable economic growth.